Wear-friction properties of friction pairs in disc-pad brakes - Kindrachuk, Myroslav; Volchenko, Dmytro; Fidrovska, Nataliia; Dukhota, Oleksandr; Zhuravlev, Dmytro; Ostashuk, Mykola; Porokhovskyi, Yurii; Kharchenko, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports data on the dynamic coefficient of friction and wear of materials of different types of friction pads and brake discs obtained from experimental research during braking under bench conditions. It was established that on the basis of the chemical composition of the materials of the friction pads with codes, in the temperature range of 100–450 °C with a step of 50 °C, the ratio of the maximum to the minimum wear of the disc varies from 6.0 to 10.0. The value of the disc wear ratio at 800 and 1000 brakings, respectively, in the temperature range of 100–250 °C and 100–450 °C was 7.6 and 14.0. This indicates that for pad materials of type A, B, C, and D under the second thermal regime, the linear wear of the working surfaces of the discs is greater than under the first thermal regime. And for the pad materials of type E and F, the wear of the discs was the same. This indicates that the use of traditional pads is characterized by a higher thermal tension of the disc brake friction pair; the absolute temperature values are in the unfavorable zone of 400–700 °C. That, in turn, could lead to both phase changes and thermal fatigue aging of materials and, as a result, to the deterioration of their tribological and thermophysical characteristics in operation. Thus, the implementation of the method of selecting pad components could improve the performance of disc brake devices of cars